2018
DOI: 10.5194/nhess-18-445-2018
|View full text |Cite
|
Sign up to set email alerts
|

Process-based modelling to evaluate simulated groundwater levels and frequencies in a Chalk catchment in south-western England

Abstract: Abstract. Chalk aquifers are an important source of drinking water in the UK. Due to their properties, they are particularly vulnerable to groundwater-related hazards like floods and droughts. Understanding and predicting groundwater levels is therefore important for effective and safe water management. Chalk is known for its high porosity and, due to its dissolvability, exposed to karstification and strong subsurface heterogeneity. To cope with the karstic heterogeneity and limited data availability, speciali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 85 publications
2
9
0
Order By: Relevance
“…Piezometric levels obtained by KAGIS reported good agreement between the observed and simulated values. Similar trustworthy results were also obtained in the simulation of the karst groundwater levels in previous studies (e.g., Adinehvand, Raeisi, & Hartmann, 2017;Brenner, Coxon, Howden, Freer, & Hartmann, 2018). In the present study, main differences between the observed and simulated values were identified between September 2009 and September 2011, probably related to the abovementioned problems in the measurement of the experimental values.…”
Section: Modelled Resultssupporting
confidence: 92%
“…Piezometric levels obtained by KAGIS reported good agreement between the observed and simulated values. Similar trustworthy results were also obtained in the simulation of the karst groundwater levels in previous studies (e.g., Adinehvand, Raeisi, & Hartmann, 2017;Brenner, Coxon, Howden, Freer, & Hartmann, 2018). In the present study, main differences between the observed and simulated values were identified between September 2009 and September 2011, probably related to the abovementioned problems in the measurement of the experimental values.…”
Section: Modelled Resultssupporting
confidence: 92%
“…The study reinforces the concept that the chalk aquifer is heterogeneous and should be treated as a karst aquifer (e.g., El Janyani et al, 2014;Valdes et al, 2014;Chédeville et al, 2015;Delbart et al, 2016;Grube et al, 2017 andBrenner et al, 2018). The evidence from our study indicates that conduit development in the Chalk is often guided by hardgrounds, sheet/semi-tabular flint bands and marl seams (section 5.1).…”
Section: Implications For Chalk Hydrogeologysupporting
confidence: 88%
“…In practice, in many areas, the functioning of the Chalk groundwater system is rather more similar to a karst aquifer than a granular or single porosity media (Bloomfield et al, 2013;Barhoum et al, 2014). Flow velocities measured from tracer tests can be >300-400 m h -1 (Maurice et al, 2006;Keim et al, 2012) and spring discharges in excess of 5 m 3 s −1 (Brenner et al, 2018). For these reasons, an increasing number of hydrogeological studies consider the Chalk as a triple porosity aquifer, with a combination of fracture and matrix porosity, and localized karst permeability (Mangin, 1975;Pennequin et al, 2017), or just as a karst aquifer in which karstification is less well developed than in other more massive and indurated limestones (Maurice et al, 2006;El Janyani et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jackson et al (2015) utilised a distributed ZOOMQ3D groundwater model of the chalk aquifer, with various emission scenario input data, to investigate the predicted changes in groundwater levels. Brenner et al (2018) conducted a further study of this chalk catchment and showed that projected climate changes may lead to generally lower groundwater levels and a reduction in exceedances of high groundwater level percentiles in the future. Chen et al (2018) conducted a study into the effects of climate change on alpine karst using GCM data.…”
Section: Introductionmentioning
confidence: 99%